Knowledge of General Dental Practitioners and Specialists in Emergency Management of Traumatic Dental Injuries - Hamonari, Nasreen (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To assess the knowledge level of general dental practitioners and specialists regarding the emergency management of traumatic dental injuries. METHODOLOGY: A cross-sectional study was conducted in Erbil City between May 2024 and August 2024, utilizing convenience sampling to collect data from dentists, including general practitioners and specialists, in various settings such as specialized dental centres, clinics, and dental schools. Data collection involved distributing 180 self-administered questionnaires to the participants. The questionnaire consisted of two sections: the first covered demographic details, including age, gender, type of practice (general dental practitioner or specialist), specific dental specialty (if applicable), practice sector, and experience. The second part included 12 questions to assess proficiency in managing dental emergencies involving luxation injuries (intrusion and extrusion), complicated crown fractures, and avulsion injuries. RESULTS: Specialists demonstrated greater proficiency in managing luxation injuries than general dental practitioners (GDPs), with a significant difference in managing avulsion injuries. Specialty was the only factor significantly affecting mean knowledge scores (P < 0.001). Male gender, experience (<5 years and 5-10 years), and public sector employment had negative but not statistically significant effects on high knowledge (P-values: 0.636, 0.289, 0.526, 0.579), respectively. CONCLUSION: The study suggests that many general dental practitioners require additional experience treating avulsed teeth. Implementing continuous education programs to ensure dentists can effectively manage avulsion injuries is highly recommended. These programs are designed to enhance practitioners' skills and knowledge in dental trauma management, ultimately leading to improved patient care and outcomes in this critical area of dentistry.